The prevention and treatment of glucocorticoid-induced osteopaenia in juvenile rheumatic disease: A randomised double-blind controlled trial. (July 2019) - Rooney, Madeleine; Bishop, Nick; Davidson, Joyce; Beresford, Michael W.; Pilkington, Clarissa; McDonagh, Janet; Wyatt, Sue; Gardner-Medwin, Janet; Satyapal, Rangaraj; Clinch, Jacqui; Foster, Helen; Elliott, Mark; et al.
Abstract: Background: Children and young people (CYP) with chronic rheumatic conditions; Juvenile Idiopathic Arthritis, Juvenile Systemic Lupus Erythematosus, Juvenile Dermatomyositis and Juvenile Vasculitis, treated with steroids, have low bone density, increased fracture risk and are likely to have suboptimal peak bone mass. There is currently no evidence base for the management of steroid-induced bone loss in children with rheumatic diseases. Methods: We undertook a multi-centre double dummy double-blind randomised placebo controlled trial to investigate whether the bisphosphonate risedronate was superior to alfacalcidol or calcium and vitamin D supplementation in the prevention and treatment of steroid-induced osteopaenia in these children. Patients were stratified and randomised in a 1:1 ratio, into: placebo; alfacalcidol; risedronate. The primary outcome was the change in lumbar spine bone mineral density z score (LSaBMDz) measured by dual energy x-ray absorptiometry at one year. Secondary outcome was fracture rate. Results: Two hundred and seventeen patients were recruited to the study. Seventy seven placebo, 71 alfacalcidol, and 69 risedronate. Highly statistically significant differences were observed in the change in LSaBMDz between the placebo and risedronate groups; 0.274, 95% CI (0.061, 0.487) (p < 0.001) and between the risedronate and the alfacalcidol groups; 0.326 95% CI (0.109, 0.543) (p < 0.001). The difference observed between the alfacalcidol and placebo group was not statistically significant. Highly statistically significant differences were seen in the change in Total Body Less Head aBMD-Z Score between the placebo and risedronate groups (p < 0.01) but not between the alfacalcidol and risedronate groups. No significant differences in fracture frequency, adverse or serious adverse reactions were observed between the groups. Conclusions: Children and adolescents receiving steroids for rheumatic diseases benefit from prophylactic treatment with bisphosphonates to increase LSaBMD. Alfacalcidol is ineffective. Highlights: First randomised controlled trial into the prevention and treatment of steroid-induced osteopenia in children. Risedronate significantly increases BMD z score compared to Vit D analogues and placebo Vit D analogues do not increase BMDz scores over placebo. The bisphosphonate Risedronate was well tolerated and no significant side effects were observed.